Cholesterol and oxysterol sulfates: Pathophysiological roles and analytical challenges. (6th September 2020) - Sanchez, Lorena Diaz; Pontini, Lorenzo; Marinozzi, Maura; Sanchez‐Aranguren, Lissette Carolina; Reis, Ana; Dias, Irundika H.K.
Abstract : Cholesterol and oxysterol sulfates are important regulators of lipid metabolism, inflammation, cell apoptosis, and cell survival. Among the sulfate‐based lipids, cholesterol sulfate (CS) is the most studied lipid both quantitatively and functionally. Despite the importance, very few studies have analysed and linked the actions of oxysterol sulfates to their physiological and pathophysiological roles. Overexpression of sulfotransferases confirmed the formation of a range of oxysterol sulfates and their antagonistic effects on liver X receptors (LXRs) prompting further investigations how are the changes to oxysterol/oxysterol sulfate homeostasis can contribute to LXR activity in the physiological milieu. Here, we aim to bring together for novel roles of oxysterol sulfates, the available techniques and the challenges associated with their analysis. Understanding the oxysterol/oxysterol sulfate levels and their pathophysiological mechanisms could lead to new therapeutic targets for metabolic diseases. LINKED ARTICLES: This article is part of a themed issue on Oxysterols, Lifelong Health and Therapeutics. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.16/issuetoc